A Large Transposon Insertion in the stiff1 Promoter Increases Stalk Strength in Maize - Zhang, Zhihai; Zhang, Xuan; Lin, Zhelong; Wang, Jian; Liu, Hangqin; Zhou, Leina; Zhong, Shuyang; Li, Yan; Zhu, Can; Lai, Jinsheng; Li, Xianran; Yu, Jianming; et al. (The Plant cell, 2020)
Stalk lodging, which is generally determined by stalk strength, results in considerable yield loss and has become a primary threat to maize (Zea mays) yield under high-density planting. However, the molecular genetic basis of maize stalk strength remains unclear, and improvement methods remain inefficient. Here, we combined map-based cloning and association mapping and identified the gene stiff1 underlying a major quantitative trait locus for stalk strength in maize. A 27.2-kb transposable element insertion was present in the promoter of the stiff1 gene, which encodes an F-box domain protein. This transposable element insertion repressed the transcription of stiff1, leading to the increased cellulose and lignin contents in the cell wall and consequently greater stalk strength. Furthermore, a precisely edited allele of stiff1 generated through the CRISPR/Cas9 system resulted in plants with a stronger stalk than the unedited control. Nucleotide diversity analysis revealed that the promoter of stiff1 was under strong selection in the maize stiff-stalk group. Our cloning of stiff1 reveals a case in which a transposable element played an important role in maize improvement. The identification of stiff1 and our edited stiff1 allele pave the way for efficient improvement of maize stalk strength.
Keywords: alely; Alleles; rostlinné geny; transformace genetická; Promoter Regions, Genetic; Genes, Plant; CRISPR-Cas Systems; Zea mays; promotorové oblasti (genetika); Cell Wall; Plant Proteins; CRISPR-Cas systémy; Transformation, Genetic; Lignin; Chromosome Mapping; sekvenční analýza; Phenotype; Sequence Analysis; buněčná stěna; fenotyp; lignin; transpozibilní elementy DNA; rostlinné proteiny; kukuřice setá; Quantitative Trait Loci; mapování chromozomů; DNA Transposable Elements; lokus kvantitativního znaku